2011
DOI: 10.1039/c1ce05024a
|View full text |Cite
|
Sign up to set email alerts
|

In situ synchrotron radiation X-ray diffraction study of crystallization kinetics of polymorphs of 1,3-dioleoyl-2-palmitoyl glycerol (OPO)

Abstract: We examined the influence of kinetics on the polymorphic behavior of 1,3-dioleoyl-2-palmitoyl glycerol (OPO), a triacylglycerol (TAG) present in natural oils such as olive oil and human breast milk. Pure OPO was heated at 15ºC• min-1 in all cases. The polymorphic crystallization of OPO was studied at different cooling rates (15º, 2º, 1º, and 0.5ºC• min-1), and the dynamic polymorphic transformations were characterized on heating by simultaneously using Differential Scanning Calorimetry (DSC) and Synchrotron Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 29 publications
6
38
1
Order By: Relevance
“…Mixtures showing the two 001 reflections of 0.65 OPO and 0.75 OPO mixtures, the intensity of the 63.5 Å line increased dramatically relatively to the 42.5 Å line from~0.01 to 1.5 as OPO ratio was increased (Table 5) clearly indicating an OPO-rich phase origin. Similarly to what was published for the triple chain structure of the OPO [13,40], the 63.5 Å line is undoubtedly associated with the b-form of OPO, and specifically to its highest stability b 1 -form. The coexistence of these two crystal structures in these mixtures can be directly related to the two phases observed in their microstructure observed by PLM (see Section 3.1.).…”
Section: Lamellar Packingmentioning
confidence: 68%
“…Mixtures showing the two 001 reflections of 0.65 OPO and 0.75 OPO mixtures, the intensity of the 63.5 Å line increased dramatically relatively to the 42.5 Å line from~0.01 to 1.5 as OPO ratio was increased (Table 5) clearly indicating an OPO-rich phase origin. Similarly to what was published for the triple chain structure of the OPO [13,40], the 63.5 Å line is undoubtedly associated with the b-form of OPO, and specifically to its highest stability b 1 -form. The coexistence of these two crystal structures in these mixtures can be directly related to the two phases observed in their microstructure observed by PLM (see Section 3.1.).…”
Section: Lamellar Packingmentioning
confidence: 68%
“…Therefore, it was suggested that this peak was a triple‐chain‐length structure and β‐form of OPO (β‐3 OPO) (Table ). The study by Bayés‐García, Calvet, Cuevas‐Diarte, Ueno, and Sato () reported that OPO did not crystallize as a β‐form under cooling at 5 °C min −1 . The presence of the β‐form of MC crystals should accelerate the nucleation rate of β‐3 OPO.…”
Section: Resultsmentioning
confidence: 99%
“…This behaviour was measured with precision for tripalmitoyl glycerol (PPP) (Sato and Kuroda, 1987) and for the other fat crystals (Blaurock, 1999 analysis also showed polymorph-dependent crystallisation kinetics of various natural fats (Foubert et al, 2008). DSC and a synchrotron radiation X-ray diffraction study of POP clearly measured the polymorph-dependent crystallisation rates of OPO, POP, OOO and OOL (L: linoleic) (Bayes-Garcia et al, 2011, 2013a.…”
Section: Polymorphic Crystallisation Of Fatsmentioning
confidence: 99%